Pyruvate kinase expression (PKM1 and PKM2) in cancer-associated fibroblasts drives stromal nutrient production and tumor growth - Chiavarina, Barbara (Landes Bioscience, 2011)
We have previously demonstrated that enhanced aerobic glycolysis and/or autophagy in the tumor stroma supports epithelial cancer cell growth and aggressive behavior, via the secretion of high-energy metabolites. These nutrients include lactate and ketones, as well as chemical building blocks, such as amino acids (glutamine) and nucleotides. Lactate and ketones serve as fuel for cancer cell oxidative metabolism, and building blocks sustain the anabolic needs of rapidly proliferating cancer cells. We have termed these novel concepts the “Reverse Warburg Effect,” and the “Autophagic Tumor Stroma Model of Cancer Metabolism.” We have also identified a loss of stromal caveolin-1 (Cav-1) as a marker of stromal glycolysis and autophagy. The aim of the current study was to provide genetic evidence that enhanced glycolysis in stromal cells favors tumorigenesis. To this end, normal human fibroblasts were genetically-engineered to express the two isoforms of pyruvate kinase M (PKM1 and PKM2), a key enzyme in the glycolytic pathway. In a xenograft model, fibroblasts expressing PKM1 or PKM2 greatly promoted the growth of co-injected MDA-MB-231 breast cancer cells, without an increase in tumor angiogenesis. Interestingly, PKM1 and PKM2 promoted tumorigenesis by different mechanism(s). Expression of PKM1 enhanced the glycolytic power of stromal cells, with increased output of lactate. Analysis of tumor xenografts demonstrated that PKM1 fibroblasts greatly induced tumor inflammation, as judged by CD45 staining. In contrast, PKM2 did not lead to lactate accumulation, but triggered a “pseudo-starvation” response in stromal cells, with induction of an NFκB-dependent autophagic program, and increased output of the ketone body 3- hydroxy-buryrate. Strikingly, in situ evaluation of Complex IV activity in the tumor xenografts demonstrated that stromal PKM2 expression drives mitochondrial respiration specifically in tumor cells. Finally, immuno-histochemistry analysis of human breast cancer samples lacking stromal Cav-1 revealed PKM1 and PKM2 expression in the tumor stroma. Thus, our data indicate that a subset of human breast cancer patients with a loss of stromal Cav-1 show profound metabolic changes in the tumor microenvironment. As such, this subgroup of patients may benefit therapeutically from potent inhibitors targeting glycolysis, autophagy and/or mitochondrial activity (such as metformin).